Comprobación de la efectividad de un probiótico elaborado artesanalmente frente a vibrios que afectan al camarón - Becerra Arrobo, Williams Mauricio (2010)
In this investigation you focuses in the results that they could be given in the confrontation of a probiótico elaborated handmadely with isolated Vibrios of shrimps and camaronera water, in which the samples were taken of the camaronera Pto. Get paid, of the parish Pto. Bolivar, canton Machala, and the development of the thesis is carried out it in the Acuacultura laboratory, Ability of Agricultural Sciences, Technical University of Machala, located in the kilometer 4 ½ from the road to Passage, in the canton Machala, county The Gold. The duration of the investigation lasts month and beginning August of the year 20 2009, considering three objectives that were: to elaborate a probiótico handmadely with the help of existent microorganisms in the camaronera floor, identification of the goods that you/they compose the probiótico and to confront the probiótico elaborated with three species of Vibrios that affect the shrimp. As a result: you elaborates the handmade probiótico of camaronera mud, you identifies two goods of present microorganisms in the probiótico like: Bacillus, and Sacharomyces cerevisae (yeast) with a percentage bigger than Bacillus, of the confrontation, in the statistical analysis of the test of t - student, is that the outlined hypothesis is accepted: The probiótico handmade is effective in the decrease of the species of Vibrios.